Development of run-time UML for JAVA programming language - Mohd Nor, Sulaiman; Hani, Mohamed Khalil; Ashourian, Mohsen; Goh, Hock Ann (2000)
Run-time modeling is a method of using the execution data for modeling the real process going on in a program. This paper introduces a run-time modeling scheme as a tool for software visualization and the Unified Modeling Language (UML) is selected to accomplish this concept. To develop a run-time UML, it is necessary to devise user-friendly methods for showing static and dynamic modeling diagrams by mapping source code information and real time execution data to UML diagrams. The proposed scheme is planned to be implemented into an integrated development environment (IDE) using Java